2018
DOI: 10.1016/j.aninu.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thyme and ajwain as antibiotic growth promoter substitutions on growth performance, carcass characteristics and serum biochemistry in Japanese quails ( Coturnix japonica )

Abstract: The present study was to evaluate thyme and ajwain as antibiotic growth promoter substitutions on growth performance, carcass characteristics and serum biochemistry in Japanese quails (Coturnix japonica). A feeding trial was conducted over 28 d with 4 groups of Japanese quails fed experimental diets formulated to provide no supplementation (control), or control + 55 mg zinc bacitracin/kg, 2 g thyme/kg, and 2 g ajwain/kg. At 35 d of age, 2 quails from each replicate were sacrificed and eviscerated. Liver, empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
11
1
2
Order By: Relevance
“…This response may be due to the active substances in the medicinal plants with highly odours and pungent taste (Mehri, Sabaghi, & Bagherzadeh‐Kasmani, 2015a). In a study with Japanese quails and in contrast with our results, it is observed that the effect of ajwain powder on the performance criteria was negligible (Kheiri et al, 2017). Although the underlying mechanisms by which phytogenics affect bird performance is not yet clear, it is documented that the variation in poultry responses to the aromatic plant seeds may be related to the chemical composition of the various seeds, environmental parameters, bird type and diet form (Behnamifar, Rahimi, Karimi Torshizi, Hasanpor, & Mohamadzade, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This response may be due to the active substances in the medicinal plants with highly odours and pungent taste (Mehri, Sabaghi, & Bagherzadeh‐Kasmani, 2015a). In a study with Japanese quails and in contrast with our results, it is observed that the effect of ajwain powder on the performance criteria was negligible (Kheiri et al, 2017). Although the underlying mechanisms by which phytogenics affect bird performance is not yet clear, it is documented that the variation in poultry responses to the aromatic plant seeds may be related to the chemical composition of the various seeds, environmental parameters, bird type and diet form (Behnamifar, Rahimi, Karimi Torshizi, Hasanpor, & Mohamadzade, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…(Valiollahi et al, 2014) came to the same result in broilers where dietary inclusion of ajwain powder decreased the E. coli population and increased the cfu of Lactobacilli . It is reported that the positive effect of medicinal plants, such as ajwain on the growth performance of broiler chickens, may be due to the antibacterial and antioxidant properties via photogenic agents (Kheiri et al, 2017). These phytogenic agents may exert either inhibitory or stimulatory effects on the harmful bacteria and endogenous secretion of the gut, respectively, through the functional substances including alkaloids, phenolic compounds, terpenoids and triterpene saponins (Ghazaghi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-feed antibiotics (IFA) have been used in poultry feeds for many years widespread at sub-therapeutic doses for their affirmative influences on growth performance, and health status of the birds (Franti et al 1971;Ghalamkari et al 2012;Goodarzi et al 2014;Yazdi et al 2014aYazdi et al , 2014bForoutankhah et al 2019). The IFA are purported to enhance the performance of the birds by decreasing the proliferation of pathogenic bacteria in the gut, resulting in greater digestion, absorption and metabolism of nutrients (Gheisari et al 2017;Kheiri et al 2018). Although including IFA in poultry diets resulted in some beneficial influences on poultry performance, the continuous utilisation resulted in increment of cross-resistance and multifold antibiotic resistance in pathogenic bacteria (Sørum and Sunde 2001), deposition of drug in poultry meat, and dysbacteriosis (Andremont 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, o uso contínuo de APC com intuito alimentar, levantou-se dúvidas e questionamentos relacionado a resistência cruzada que ocasionalmente acometeria os seres humanos com desenvolvimento de bactérias resistentes (Kheiri et al, 2018). A proibição ou retirada voluntária dos APC, em diversos países foram retificadas nos diversos órgãos regulatórios, sendo 128 países com medidas crescentes de restrição (Salim et al, 2018).…”
Section: Introductionunclassified